Recurrent Herpetic Stromal Keratitis in Mice: A Model for Studying Human HSK. (17th April 2012) - Stuart, Patrick M.; Keadle, Tammie L.
Abstract : Herpes simplex virus 1 (HSV-1) infection of the cornea leads to a potentially blinding disease, termed herpetic stromal keratitis (HSK) that is characterized by lesions of an immunoinflammatory nature. In spite of the fact that HSK typically presents as a recurrent disease due to reactivation of virus which latently infects the trigeminal ganglia, most murine studies of HSK have employed a primary and not recurrent model of the disease. This report documents the several recurrent models of HSK that have been developed and how data generated from these models differs in some important aspects from data generated following primary infection of the cornea. Chief among these differences is the fact that recurrent HSK takes place in the context of an animal that has a preexisting anti-HSV immune response, while primary HSK occurs in an animal that is developing such a response. We will document both differences and similarities that derive from this fundamental difference in these models with an eye towards possible vaccines and therapies that demonstrate promise in treating HSK.